Ampleur et impact de l’économie de la connaissance à Bruxelles - Tom Van Puyenbroeck; Johan Eyckmans; Peter Teirlinck; André Spithoven; Gilles Van Hamme (Brussels Studies)
We analyse the extent, growth and spatial distribution of knowledge-intensive employment in the Brussels Capital region and larger Brussels metropolitan area and compare it to its neighbouring geographical entities. We look at its impact on total employment, using both econometric and input-output analysis. Close to one out of two jobs in Brussels can be regarded as knowledge intensive. Over the period 2008-2020, the compound annual growth rate of knowledge-intensive employment was highest in the surrounding Brussels functional metropolitan area. A strong concentration of several knowledge services can be found in the Brussels metropolitan area, with different location patterns. Finance remains very central in the Brussels metropolitan areas, while others favour peripheral location, as it is the case for the pharmaceutical and accounting industry. A negative total employment growth rate differential between Brussels and the rest of Belgium is due to an industry-mix effect. Each additional knowledge intensive job in Brussels can be associated with the creation of another two jobs. For jobs generated by knowledge intensive sectors, forty percent of the extra employment within Brussels is accruing to less knowledge intensive labour.